Dracontius et les Vandales : résistance, médiation, échec - Giampiero Scafoglio (Cahiers Mondes Anciens)
In Dracontius’ works, we recognize the different attitudes adopted by an Afro-Roman intellectual who seeks a dialogue with the Vandal power and tries to propose a modus uiuendi between (Arian) rulers and (Catholic) people. The praise of a (real or desired) project of cultural integration based on the school of rhetoric and Roman tradition (Romulea, 1) then leaves place to the complaint and denunciation of despotism and abuses of power (Controuersia de statua uiri fortis). Later, during his captivity, the poet addresses the Vandal king an earnest request for forgiveness, which also constitutes a smart political proposal aimed at promoting a peaceful coexistence between Arians and Catholics (Satisfactio). The pathetic failure of this attempt drives him to take an uncompromising position, resolutely opposing to Arianism in the name of the Nicene Creed (Laudes Dei).